Reinforcing or counterproductive behaviors for sustainable entrepreneurship? The influence of causation and effectuation on sustainability orientation - Matthew P. Johnson; Jacob Hörisch (Business Strategy and the Environment, 2021)
Effectuation, as an emerging theoretical approach in entrepreneurship, is receiving increasing attention in research and practice. Still, the integration of effectuation in sustainable entrepreneurship literature is sparse, and its influence on the sustainability orientation of ventures has so far not been examined in the academic literature. This article, therefore, investigates the influence that causal and effectual behaviors have on the sustainability orientation of established entrepreneurial ventures. This is important to consider, especially if entrepreneurial behaviors were to influence sustainability orientation negatively, this could potentially thwart the venture's ability to create lasting sustainability value. Based on a quantitative survey among 140 sustainable ventures, we find support for the hypothesis that causal behaviors reinforce sustainability orientation. We demonstrate that effectual behaviors exert a positive influence on sustainability orientation as well. Thus, the experimentation and flexibility of goals that ventures possess reflect that effectual behaviors are not at the expense of sustainability orientation. These results can inform sustainable entrepreneurs and educators to use both behaviors purposefully and highlight causal and effectual behaviors are equally important elements for sustainable entrepreneurship education.
Keywords: 330; causation; effectuation; experimentation; flexibility; sustainability orientation; sustainable entrepreneurship